Magnetic resonance imaging of colonic function - Placidi, Elisa (2011)
The overall aim of this work was to develop MRI methods and techniques to study the physiology and the pathology of the gastrointestinal tract, with particular attention to the colon. Besides, the development of new methods was aimed in order to perform quantitative analysis using proton and fluorine MRI. In particular the first experimental chapter describes the development and the optimisation of imaging protocols for studying colonic function in undisturbed physiologically relevant conditions. In addition a texture analysis method based on Gabor filters is developed and used for the objective assessment of colonic content characteristics. The mechanisms of action of common anti-diarrhoeal and anti-constipation agents are also investigated. The last experimental chapter describes the development of methods for using markers to measure GI transit. Transit time, i.e. the time it takes for a marker to pass through the entire gut, is often affected by functional gastrointestinal disorders, therefore it is of primary importance to develop a non-invasive and effective technique for the diagnosis of such gastrointestinal diseases. The use of fluorinated agents and its many advantages compared to other techniques is outlined and the first in vivo studies at high field are presented. The use of gadolinium based compounds as an additional marker is also discussed.